The Discourse of Tahrif al-Qur’an in Indonesian Syiah Communities: A Study on IJABI and ABI Perspectives - Muhammad Irfanudin Kurniawan; Ainur Rha'in; Obydur Rahman (Walidem Institute and Publishing, 2025)
Objective: The purpose of this study is to explain the theological attitude of the Indonesian Syiah community, especially the Indonesian Ahlul Bait Jamaah Association (IJABI) and the Indonesian Ahlul Bait (ABI), towards the doctrine of tahrif al-Qur'an and analyze how their interpretation affects the public perception of Syiah in Indonesia. Theoretical framework: This study uses a theological-sociological framework by combining doctrinal analysis and sociological perspectives of religion. This approach is used to understand the relationship between beliefs, identity, and community dynamics in the context of Indonesian Syiah. Literature review: This study examines the historical debate on tahrif in the Syiah scholarly tradition, ranging from the classical view that indicates textual changes to contemporary perspectives that expressly reject the idea. In addition, this study also reviews various studies on Syiah in Indonesia that have so far focused on issues of identity politics, sectarian conflicts, and minority rights. Thus, this study is here to fill the study gap related to the sensitive issue of tahrif al-Qur'an in the context of Indonesia. Results: The results of the study show that both IJABI and ABI reject the doctrine of tahrif al-Qur'an and affirm the authenticity of the current Qur'anic text, so that they are within the Sunni consensus line. Nevertheless, differences arise in the way they articulate and communicate those views. IJABI emphasizes a dialogical and moderatory approach to reduce public suspicion, while ABI emphasizes a more formal theological defense based on Syiah Imamiyah orthodoxy. Implications: This study shows that the Syiah community in Indonesia consciously positions itself within the framework of Islamic unity to dismiss accusations of heterodoxy. This attitude contributes to reducing sectarian tensions and strengthening inter-religious harmony in Indonesia. Novelty: The novelty of this research lies in a comparative analysis that focuses on the doctrinal discourse of tahrif al-Qur'an in the two main Syiah organizations in Indonesia. This study shows how minority groups seek to negotiate theological legitimacy in the context of Indonesia's majority Sunni society.